Pengaruh Inovasi Material Ramah Lingkungan terhadap Kualitas Bangunan di Indonesia dalam Perspektif Undang-Undang Jasa Konstruksi - Krisdiyanto, Aris (LPPM Institut Pendidikan Nusantara Global, 2025)
Innovation in environmentally friendly materials has become a crucial aspect of Indonesia’s construction industry, particularly within the context of Law No. 2 of 2017 on Construction Services, which emphasizes sustainability and building quality. This study aims to analyze the impact of implementing eco-friendly materials on building quality in Indonesia by considering structural aspects, energy efficiency, and compliance with construction service regulations. The research method combines a survey of 150 construction professionals with laboratory testing of three innovative materials: green concrete, recycled steel, and natural fiber panels. The results show that the use of environmentally friendly materials increases energy efficiency by up to 30% and structural quality by 15%. Green concrete exhibits 15% higher compressive strength, recycled steel demonstrates corrosion resistance of up to 92%, and natural fiber panels provide thermal efficiency of 80%. A total of 78% of respondents support the use of innovative materials, although 60% still consider cost and availability constraints. This study confirms that the application of eco-friendly materials aligns with the provisions of the Construction Services Law, thereby requiring policy support to optimize production costs and strengthen supply chains for broader implementation, particularly in rural areas.